Development of latent fingermarks by electrochemical deposition of nickel on brass surfaces - Jevtić, Tamara S.; Lamovec, Jelena S.; Bjelovuk, Ivana D. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose of the research: Latent fingermarks can be found on the crime scene on various surfaces and made visible by different forensic methods. As this evidence can often be found on brass surfaces (ammunition casings, decorative items, etc.) the paper discusses the possibilities of applying electrochemical deposition of nickel on brass. The condition for the application of this technique is the existence of a conductive substrate. Fatty components of latent fingermarks have insulating properties and prevent the electrodeposition process. Methods: Experimental thin rectangular pieces of brass foil were used as substrates for latent fingermarks. Samples were degreased in acetone and ethyl alcohol, rinsed in deionized water, and dried in a stream of compressed air before leaving the fingermarks. To enhance the presence of sweat on friction ridges, the hand was placed in the silicone glove for five minutes. A slight touch of the index finger was left on the tiles. Fingermarks were developed on brass samples by fingerprint powder and the electrochemical deposition of nickel on another brass surface simultaneously. In order to obtain the best possible evidence, the parameters affecting the deposition rate (current density, deposition time) were changed until a clear fingermark was obtained.Results: The fingermarks were compared visually using a magnifying glass with illumination to observe the contrast between the papillary lines and the interpapillary space and the characteristic details (minutiae). The optimal results were achieved with the current density (deposition rate) of 50mA/cm2 for 10s. Conclusion: Electrochemical deposition of nickel on brass is an applicable technique for developing latent fingermarks with certain limitations.
Keywords: latent fingermarks; interpapillary space; brass; fingermark development; electrochemical deposition